Breast Cancer Survival Analysis Using Cox Proportional Hazard Regression and Kaplan Meier Method - Farida, Yuniar; Maulida, Eka Agustina; Desinaini, Latifatun Nadya; Utami, Wika Dianita; Yuliati, Dian (Universitas Muhammadiyah Mataram, 2021)
Breast cancer is one of the malignant tumors that begins in the breast cells that develop and attack the surrounding tissues; according to World Health Organization (WHO), breast cancer is globally declared the top five killer cancers. In Indonesia, breast cancer becomes the number one killer cancer. One of the successes in breast cancer treatment is if the cure obtained by cancer patients can be proven to have the same life expectancy as those who do not have breast cancer.This study aims to know the probability of survival of breast cancer patients and know the factors that affect breast cancer patients' survival. The data were consist of 394 medical records of breast cancer patients at Dr. Soetomo Hospital Surabaya in the period January 2018 – December 2019, with variables used, i.e., initial age of infection, clinical stage, tumor size, metastatic to other organs, type of treatment, and patient status (life or death). This study using Kaplan Meier and Cox Proportional Hazard regression methods, and the result showed that the probability of survival of breast cancer patients (with data samples) was 0.737 or 73.7%. The variables that significantly affect breast cancer patients' survival are the initial age of infection, the clinic stage, and the tumor's size. This research provides information and motivation to the community related to life expectancy, especially in breast cancer patients, to stay motivated in the healing process. In addition, this research is also used to add insight to academics, especially the department of statistics, regarding the regression of Cox Proportional Hazard in analyzing the survival of breast cancer patients.